Enhancing psychological resilience and reducing maladaptation in war-exposed young adults: a randomized controlled trial in Ukraine - Sodolevska Валерія (Psychosomatic Medicine and General Practice, 2025)
Background. The full-scale war in Ukraine has led to a substantial increase in the psychological burden on young people, manifested in the high prevalence of anxiety–depressive disorders and post-traumatic stress disorder. Youth represent a critical developmental period, underscoring the need for targeted rehabilitation programs. Objective. To enhance the effectiveness of medical and psychological support for young people through the development and evaluation of a resilience-oriented program aimed at reducing maladaptive symptoms and strengthening psychological resources. Materials and Methods. A randomized controlled trial was conducted with 146 participants aged 18–35 years who exhibited psychological maladaptation due to the war in Ukraine. Participants were randomly assigned to either the intervention group (n=73; standard treatment plus resilience-oriented intervention) or the comparison group (n=73; standard treatment only). The intervention comprised five 60-minute sessions focusing on psychoeducation, emotional self-regulation, mindfulness techniques, and cognitive reframing of adverse experiences. Validated psychometric instruments were employed to assess outcomes (PHQ-9, GAD-7, IES-R, CD-RISC-10, CQLS). Results. After 35 days, the intervention group demonstrated a statistically significant reduction in depression, anxiety, and post-traumatic stress symptoms (p<0.01), alongside significant improvements in resilience and quality of life (p<0.001), compared with the comparison group. Linear mixed-effects models confirmed the robustness of these findings after adjusting for sociodemographic covariates. Conclusions. The resilience-oriented program showed high effectiveness in alleviating maladaptation symptoms and enhancing adaptive resources among war-affected youth. These findings support the integration of resilience-based interventions into standard medical-psychological rehabilitation programs. At the same time, the study’s limitations (single-center design, lack of blinding, short follow-up period) highlight the need for future multicenter, longitudinal trials with more heterogeneous samples. Keywords: stress, maladaptation, resilience, youth, psychological interventions, psychological rehabilitation, war, depression, anxiety, post-traumatic stress